The Impact of the Financial Crisis on Developing Countries: Evidence from Sudan - Abbas, Nawal H. (Gezira Journal of Economic and Social Sciences; مجلد 2 عدد 2 (2011), 2011)
The financial Crisis that built up in financial markets in the developed world three years back has spread in a variety of ways into developing countries. While the global crisis has taken a little longer to reach developing and low-income countries, those countries are in the front line when it comes to suffering its bitter effects. This paper aims to appraise in a critically manner the impact of the global financial crisis on the Sudanese economy and the responses undertaken by the national authorities to mitigate its impact. The paper reviews and discusses the three mechanisms that play a key role in transmitting the crisis from developed to developing countries; trade, capital flows and remittances. The research identifies global trade as the main channel of transmission of the crisis to Sudan. Foreign Direct Investment (FDI) and workers’ remittance appear to be resilient to the financial chaos, while the Official Development Assistance flows (ODA) to the country undergo minor declines since the blast of the crisis. The analysis reveals that the Sudanese economy has been hard hit by the financial turmoil; the GDP growth rate reveals a steep declining trend, the depreciation in the exchange rate for the Sudanese pound is high, the acceleration in the inflation rate is noticeable and the fiscal and current account deficits worsen. The responses to the negative impacts of the crisis are slow and seem to lie in taking monetary and fiscal measures aiming at sustaining economic growth and maintaining monetary and financial stability. The paper suggests a number of recommendations to enhance the measures adopted and introduces new ones.